Poetic Patterns and Constituent Order in Biblical Hebrew - Atkinson, Ian (Hebrew studies, 2025)
Scholarship on constituent order in Biblical Hebrew is largely limited to the analysis of narrative prose. Those few studies which pay attention to poetic literature enjoy no consensus concerning the roles which Information Structure and poetics play in determining the clausal constituent order, nor do they concern themselves with the implications of deviant constituent order for larger patterns of discourse structure. In this paper, I argue for the analytical primacy of poetic cognition over Information Structure - which may or may not coincide one with the other. Constituent order patterns used to structure poetic discourse through shaping line groupings include repetition, symmetry and constituent-specific strategies of tail-head linkage and inclusio, of which I will illustrate with examples drawn from Psalms 1-25, 51 and 91. These structures account for non-default constituent order at the clause-level - when Information Structure lacks explanatory power - and shed light on the previously unappreciated contribution of constituent order patterns across poetic lines in determining larger discourse structures.